Role of platelet biomarkers in inflammatory response - Yufei Chen; Haoxuan Zhong; Yikai Zhao; Xinping Luo; Wen Gao (BMC, 2020)
Abstract Beyond hemostasis, thrombosis and wound healing, it is becoming increasingly clear that platelets play an integral role in inflammatory response and immune regulation. Platelets recognize pathogenic microorganisms and secrete various immunoregulatory cytokines and chemokines, thus facilitating a variety of immune effects and regulatory functions. In this review, we discuss recent advances in signaling of platelet activation-related biomarkers in inflammatory settings and application prospects to apply for disease diagnosis and treatment.